Performance control in handstands: challenging entrenched coaching strategies for young gymnasts - Rohleder, J.; Vogt, T. (International Journal of Performance Analysis in Sport, 2018)
Despite well-accepted knowledge concerning the importance of the wrists` contributions in handstand balances, common handstand coaching strategies prioritise developing the required aligned and aesthetic body shape. Thus, this study investigated the effects of a sole postural training on the maintenance compared to the execution quality in handstands in young competitive gymnasts. Therefore, twenty-two participants (13 females, aged: 8.54 ± 1.56 years; 9 males, aged: 8.67 ± 0.87 years) were randomly assigned into two counterbalanced groups, GPT (guided postural training) and CON (control), each n = 11. Within one week, GPT received four standardised training sessions (T1, T2, T3 and T4) including verbal and tactile advices addressing a straight body posture. Prior to T1 (pre-test), after T2 (mid-test) and after T4 (post-test), all participants (GPT and CON) were asked to perform five handstands where handstand executions were assessed by four gymnastics judges based on standardised video recordings which also captured the balance time. There were no group-related changes in balance time (p > .05); however, following T2, results revealed a positive impact of GPT on postural execution (p < .05). With respect to the importance of forearm activity in handstand performances, further research is needed approaching wrist-related advice in handstand acquisition.